IMPLICATIONS OF THE IMPLEMENTATION OF THE SEGAK TEST IN MALAYSIAN SECONDARY SCHOOLS - Krishnasamy, Hariharan; Veloo, Arsaythamby; Md-Ali, Ruzlan (PEOPLE: International Journal of Social Sciences, 2017)
The implementation of an effective, comprehensive standardized assessment for Physical Education has seen several challenges that need to be investigated. This study investigated qualitatively the implications of the implementation of the SEGAK test.The major focus of the study was to explore teachers’ and students’ perspectives about the SEGAK test. Based on stratified random sampling in five schools, 10 Physical Education teachers and 20 students in a selected district in Malaysia participated in the study. Interview sessions were conducted in the schools and the information they gave was analysed thematically. The findings showed that teachers generally agreed that the SEGAK test will be more effective if it can be conducted by teachers who were specifically trained in the discipline. Many teachers were non-optionists and had to familiarize themselves with the SEGAK test and acquire skills regarding the field. Most of the teachers believed that there was a dire need for more teachers who were optionists as they could better perform the tasks of evaluation under SEGAK. The students mentioned that they were aware of the SEGAK test but did not fully understand its impact on them or the health benefits of taking part in the test. Based on the findings, the study suggests that there is a need for more trained and qualified teachers for Health and Physical Education. Future research could look at schools in other states in Malaysia as such findings would be more representative of the issues related to the implementation of the SEGAK test.